The Metaphysics of Suffering - Gianni Vattimo (The European Journal of Psychoanalysis, 2017)
The author critiques the long Western tradition of exalting physical and mental pain as privileged means towards learning the essential truths. This idealization of pain, sorrow, and asceticism in general, is an essential part of Western metaphysics, and as such it has influenced Western medicine and other fields, including psychoanalysis. Heidegger’s critique of Western metaphysics can also be extended to our modern ideology of renunciation, to which the author opposes the acceptance of one’s own radical historicity.
Keywords: Being-for-Death; Heidegger; metaphysics; No Painkillers; suffering